2017
DOI: 10.3389/fmars.2017.00356
|View full text |Cite
|
Sign up to set email alerts
|

Distributional Patterns of Polychaetes Across the West Antarctic Based on DNA Barcoding and Particle Tracking Analyses

Abstract: Recent genetic investigations have uncovered a high proportion of cryptic species within Antarctic polychaetes. It is likely that these evolved in isolation during periods of glaciation, and it is possible that cryptic populations would have remained geographically restricted from one another occupying different regions of Antarctica. By analysing the distributions of nine morphospecies, (six of which contained potential cryptic species), we find evidence for widespread distributions within the West Antarctic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 102 publications
2
16
0
Order By: Relevance
“…The geographical and depth distribution of the different cryptic clades and potential species identified within this study are yet to be investigated (Brasier et al  [65]), although some biogeographic implications of these data are already evident. The presence of cryptic Antarctic clades within morphospecies described from the Northern Hemisphere including Glycera capitata, Scalibregma inflatum and Maldane sarsi indicates that we should be questioning the current ‘usual’ identifications of cosmopolitan polychaete species.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical and depth distribution of the different cryptic clades and potential species identified within this study are yet to be investigated (Brasier et al  [65]), although some biogeographic implications of these data are already evident. The presence of cryptic Antarctic clades within morphospecies described from the Northern Hemisphere including Glycera capitata, Scalibregma inflatum and Maldane sarsi indicates that we should be questioning the current ‘usual’ identifications of cosmopolitan polychaete species.…”
Section: Discussionmentioning
confidence: 99%
“…The Antarctic specimens were also collected from relatively deep waters (~200-1500 m) and showed high connectivity along the western Antarctic Peninsula, reflecting the widespread distributional patterns recently found for many cryptic polychaete species collected from a similar depth range from across the West Antarctic (Brasier et al 2017). However, Brasier et al (2017) also found species from this region with highly restricted ranges, concluding that differences in Southern Ocean species distributions are more likely to rely on a complex of factors, rather than just a single factor such as oceanographic currents.…”
Section: Within-sternaspis Relationships and Phylogeographymentioning
confidence: 74%
“…While the geographic range from eastern Australia to the GAB is likely, the apparent broad bathymetric range from shelf to abyssal depths (60–3884 m) requires further investigation as this putative depth range would extend vertically across shelf, slope and abyssal faunal zones. Genetic evidence suggests some deep-water annelids have ‘broad’ (> 2500 m sensu Glazier and Etter 2014 ) depth ranges, e.g., the maldanid Nicomache lokii range 3668 m ( Eilertsen et al 2018 ), but bathymetric ranges of other deep-sea annelid species are more restricted e.g., 1300 m for the spionid Laonice weddellia (see Brasier et al 2017 ). According to the census of abyssal polychaetes (> 2000 m), ~ 62–78% of species within a family had bathymetric ranges smaller than 1000 m ( Paterson et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%